QR code design: From digital graphics to environmental, product and fashion design - Vorobchuk, Mariia; Pashkevych, Kalina; Yezhova, Olga; Protsyk, Bogdan (Journal of Graphic Engineering and Design, 2024)
Classification of design codes by the level of complexity of their design was created for the first time. The obtained results are key to understanding the role of the QR code as a full-fledged work of art in the context of modern design. In the future, this will allow us to single out the most noticeable trends in the development of coded information in the conditions of modern visual culture.